Place of stimulating laxatives in therapy of constipations - E. Y. Plotnikova; V. N. Zolotukhina; T. Y. Gracheva (Медицинский совет, 2016)
The article provides foreign and Russian epidemiological data on constipation incidence, their reasons and classifications are considered in detail. The section Constipation Therapy describes non-pharmacological principles as well as groups of drugs that are used for this pathology. An analysis of the Russian pharmaceutical market of laxative drugs in the recent years is presented. Stimulating laxatives are used by patients more often. Sodium picosulphate is one of the major drugs from group of stimulating laxatives. Authors cite results of several studies on effectiveness of sodium picosulphate and discuss why this drug is one of the most frequently used for constipations.